Innovation of Gerhana Application Development in Technology-Based Madrasah Learning - Fitri, Laili Ifdhatul; Rohmah, Hidayatur (Institut Agama Islam Negeri Lhokseumawe, 2023)
Abstract: The purpose of this research is to develop interactive learning media called “Gerhana” (Gerakan Pembaharuan Islam di Indonesia) as android applications. The media is used to determine the feasibility of the product and student responses to the application. This research employs the APPED Research and Development Model (analysis, planning, production, evaluation, and dissemination). The instrument used is a media and material expert validation questionnaire, as well as a student response questionnaire. The instrument was administered to 30 students at the Islamic History class subject (Grade 10), at the Islamic Senior High School (ISHS) 9, Jombang. The initial media validation test generated an average score of 86 percent, while the second one resulted in 84 percent with a very valid category. The results of the initial material validation test had an average score of 92 percent, while the second one was 87 percent with very valid criteria. Further, the results of the user test in the form of a student response questionnaire resulted in average score of 80 percent with decent criteria. Therefore, according to the results of the user test and students' response suggest that the “Gerhana” application is feasible. Abstrak: Tujuan penelitian ini untuk mengembangkan media pembelajaran interaktif yang diberi nama Gerhana (Gerakan Pembaruan Islam di Indonesia) berupa aplikasi Android. Media digunakan untuk mengetahui kelayakan produk dan respon siswa terhadap aplikasi media Gerhana (Gerakan Pembaruan Islam di Indonesia) pada mata pelajaran Sejarah Islam XI di Madrasah Aliyah Negeri (MAN) 9 Jombang. Penelitian ini menggunakan metode kualitatif model penelitian dan pengembangan (Research and Development) meliputi analisis, perencanaan, produksi, evaluasi, diseminasi (APPED). Instruman yang digunakan adalah angket validasi ahli media dan materi, serta angket respon siswa. Instrumen ini diberikan kepada siswa kelas XI MAN 9 Jombang sebanyak 30 siswa. Hasil dari Penelitian dilihat dari uji validasi ahli desain media, ahli materi, dan angket respon siswa. Hasil dari uji validasi ahli media yang pertama dengan skor rata-rata 86%, yang kedua sebesar 84% dengan kategori sangat valid. Sedangkan hasil uji validasi ahli materi yang pertama dengan skor rata-rata sebesar 92%, yang kedua sebesar 87% dengan kriteria sangat valid, dan hasil dari uji penguna berupa angket respon siswa dengan skor rata-rata 80% dengan kriteria layak. Dengan demikian dilihat dari hasil uji penguna respon siswa terhadap media aplikasi Gerhana layak digunakan.